Measuring complications of serious pediatric emergencies using ICD‐10. (29th December 2020) - Michelson, Kenneth A.; Dart, Arianna H.; Bachur, Richard G.; Mahajan, Prashant; Finkelstein, Jonathan A.
Abstract: Objective: To create definitions for complications for 16 serious pediatric conditions using the International Classification of Diseases, 10th Revision, Clinical Modification or Procedure Coding System (ICD‐10‐CM/PCS), and to assess whether complication rates are similar to those measured with ICD‐9‐CM/PCS. Data Sources: The Healthcare Cost and Utilization Project State Emergency Department and Inpatient Databases from five states between 2014 and 2017 were used to identify cases and assess complication rates. Incidences were calculated using population counts from the 5‐year American Community Survey. Data Collection/Extraction Methods: Patients were identified by the presence of a diagnosis code for one of the 16 serious conditions. Only the first encounter for a given condition by a patient was included. Encounters resulting in transfer were excluded as the presence of complications was unknown. Study Design: We defined complications using data elements routinely available in administrative databases including ICD‐10‐CM/PCS codes. The definitions were adapted from ICD‐9‐CM/PCS using general equivalence mappings and refined using consensus opinion. We included 16 serious conditions: appendicitis, bacterial meningitis, compartment syndrome, new‐onset diabetic ketoacidosis (DKA), ectopic pregnancy, empyema, encephalitis, intussusception, mastoiditis, myocarditis, orbital cellulitis, ovarian torsion, sepsis, septic arthritis, stroke, and testicular torsion. Using data from children under 18 years, we compared incidences and complication rates across the ICD‐10‐CM/PCS transition for each condition using interrupted time series. Principal Findings: There were 61 314 ED visits for a serious condition; the most common was appendicitis (n = 37 493). Incidence rates for each condition were not significantly different across the ICD‐10‐CM/PCS transition for 13/16 conditions. Three differed: empyema (increased 42%), orbital cellulitis (increased 60%), and sepsis (increased 26%). Complication rates were not significantly different for each condition across the ICD‐10‐CM/PCS transition, except appendicitis (odds ratio 0.62, 95% CI 0.57‐0.68), DKA (OR 3.79, 95% CI 1.92‐7.50), and orbital cellulitis (OR 0.53, 95% CI 0.30‐0.95). Conclusions: For most conditions, incidences and complication rates were similar before and after the transition to ICD‐10‐CM/PCS codes, suggesting our system identifies complications of conditions in administrative data similarly using ICD‐9‐CM/PCS and ICD‐10‐CM/PCS codes. This system may be applied to screen for cases with complications and in health services research.